2023
DOI: 10.3847/2041-8213/acade4
|View full text |Cite
|
Sign up to set email alerts
|

CEERS Key Paper. I. An Early Look into the First 500 Myr of Galaxy Formation with JWST

Abstract: We present an investigation into the first 500 Myr of galaxy evolution from the Cosmic Evolution Early Release Science (CEERS) survey. CEERS, one of 13 JWST ERS programs, targets galaxy formation from z ∼ 0.5 to >10 using several imaging and spectroscopic modes. We make use of the first epoch of CEERS NIRCam imaging, spanning 35.5 arcmin2, to search for candidate galaxies at z > 9. Following a detailed data reduction process implementing several custom steps to produce high-quality reduced images, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(220 citation statements)
references
References 131 publications
7
177
3
Order By: Relevance
“…We use the data taken from the Cosmic Evolution Early Release Science (CEERS;Finkelstein et al 2023) that was released in 2022 June. CEERS data include four pointings covering 33.1 arcminutes 2 , with seven bands of F115W, F150W, F200W, F277W, F356W, F410M, and F444W.…”
Section: Comparison With Jwst Image Decompositionmentioning
confidence: 99%
“…We use the data taken from the Cosmic Evolution Early Release Science (CEERS;Finkelstein et al 2023) that was released in 2022 June. CEERS data include four pointings covering 33.1 arcminutes 2 , with seven bands of F115W, F150W, F200W, F277W, F356W, F410M, and F444W.…”
Section: Comparison With Jwst Image Decompositionmentioning
confidence: 99%
“…The results have been surprising: multiple independent analyses have shown that the number density of bright galaxies at z > 9 is larger than predicted by theoretical models or on the basis of the extrapolation from lower-redshift estimates (e.g., Finkelstein et al 2023;Bouwens et al 2023aBouwens et al , 2023bHarikane et al 2023;Pérez-González et al 2023). This excess is most pronounced in the brightest part of the luminosity function (LF), which seems to evolve very little from z = 4 to z = 10-12.…”
Section: Introductionmentioning
confidence: 96%
“…The publicly available NIRSpec Multi Shutter Assembly (MSA) data from the CEERS program (Program ID: 1345; Finkelstein et al 2023) were used for this analysis. These medium-resolution R ∼ 1000 data were obtained using the G140M/F100LP, G235M/F170LP, and G395M/F290LP grating and filter combinations, covering the wavelength range of λ = 1-5 μm.…”
Section: Observationsmentioning
confidence: 99%
“…In this paper, we use the first spectroscopic data from the Cosmic Evolution Early Release Science (CEERS) survey (Finkelstein et al 2023) with JWST (Section 2) to investigate the improvements in nebular reddening constraints afforded by Paschen lines (Section 3), and the implications of such constraints on the reddening of the UV continuum for galaxies at redshifts z = 1.0-3.1 (Section 4). A Chabrier (2003) initial mass function (IMF) is considered throughout the paper.…”
Section: Introductionmentioning
confidence: 99%